Expectation-driven cycles: time-varying effects - Antonello D'Agostino; Caterina Mendicino (European Central Bank (ECB), 2015)
This paper provides new insights into expectation-driven cycles by estimating a structural VAR with time-varying coefficients and stochastic volatility, as in Cogley and Sargent (2005) and Primiceri (2005). We use survey-based expectations of the unemployment rate to measure expectations of future developments in economic activity. We find that the effect of expectation shocks on the realized unemployment rate have been particularly large during the most recent recession. Unanticipated changes in expectations contributed to the gradual increase in the persistence of the unemployment rate and to the decline in the correlation between the inflation and the unemployment rate over time. Our results are robust to the introduction of financial variables in the model.
Keywords: C32; E24; E32; 330; economic fluctuations; Stochastic Volatility; survey expectations; time varying vector autoregression